The Chaos of the Prosperity Gospel: A Case Study of Two Prominent Nigerian Pastors with Churches Over 150 Countries Revealed to Be Spreading Fraudulent Gospels - Ntui-Abung, John (Wetsbow, 2017)
Over the years, John Ntui has written so many articles on Christian apologetics and defense from false teachers. On his journey, he became increasingly aware that Christianity is being ravaged by the prosperity gospels, so John decided, as a theologian and pastor, to confront the heresy of his age where Christianity is being reduced by a group of sophist to a mere meal ticket. He then decided to write in order to correct the influence of a defective Christianity in the minds of those who truly desire to know God. Join Pastor John on a ride to uncover the tricks of these false prophets who are ravaging the Gospel for their own gain and taking the lead of spreading the gospel from Africa to ends of the earth. “Americans, in their quest for a flamboyant lifestyle, invented the prosperity gospels; and Nigerians, consumed by their lust, are spreading it to the ends of the earth” (John Ntui-Abung).
paid